Bifrontal high-frequency transcranial random noise stimulation is not effective as an add-on treatment in depression. (January 2021) - Schecklmann, Martin; Nejati, Vahid; Poeppl, Timm B.; Peytard, Juliette; Rupprecht, Rainer; Wetter, Thomas C.; Langguth, Berthold; Kreuzer, Peter M.
Abstract: Background: Depressive disorders are linked to dysfunction in prefrontal cortical areas. Hence, non-invasive neurostimulation of the prefrontal cortex has demonstrated antidepressant efficacy. In the present study, we investigated the efficacy of high frequency transcranial random noise stimulation (hf-tRNS) as an add-on treatment for depression in a sham-controlled randomized trial. Methods: Forty in-patients with depression were randomized and treated with real or sham hf-tRNS (100–650 Hz) with 0 mA offset. The electrodes were mounted over the left and right dorsolateral prefrontal cortex. The Hamilton Depression Rating Scale (primary outcome), the Major Depression Inventory, the Clinical Global Impression scale and the Global Assessment of Functioning scale were used for assessment at baseline, after 3 weeks of intervention (end of treatment), and 9 weeks after intervention. Safety parameters included cognitive functioning and reported side-effects. Results: Comparison of real and sham treatment at the planned interim analysis showed an amelioration of symptoms in both groups for all outcomes with numeric but not statistically significant superiority of the sham arm for the primary outcome. Thus, the study was terminated prematurely after an interim analysis. There were no systematic differences with respect to safety parameters. Limitations: The negative finding might be related to the specific stimulation parameters used in this study. Conclusions: Our study suggests that prefrontal hf-tRNS is safe but not effective as an add-on treatment of depression. The challenge for future studies employing transcranial electric stimulation remains to identify effective stimulation parameters for the treatment of depression. Highlights: High-frequency transcranial random noise stimulation (hf-tRNS) of the prefrontal cortex. hf-tRNS is safe but not effective as an add-on treatment of depression. Identification of effective stimulation parameters is needed.